Bank Regulations Are Changing : For Better Or Worse ? - Barth, James R., 1943-2023 1943-2023 (The World Bank, 2008)
This paper presents new and official survey information on bank regulations in 142 countries and makes comparisons with two earlier surveys. The data do not suggest that countries have primarily reformed their bank regulations for the better over the last decade. Following Basel guidelines many countries strengthened capital regulations and official supervisory agencies, but existing evidence suggests that these reforms will not improve bank stability or efficiency. While some countries have empowered private monitoring of banks, consistent with the third pillar of Basel II, there are many exceptions and reversals along this dimension